Homemade bread with inclusion of different levels of shavings (cut in "v") of smoked tilapia (Research, Society and Development, 2021)
This study aimed to evaluate the physicochemical, microbiological and sensory characteristics of homemade breads with the addition of smoked tilapia shavings (cut in “V” fillet). The shavings were subjected to a smoking process with the addition of aromatic herb extract. 0%, 3%, 6% and 9% of smoked chips in homemade bread were included, being evaluated for proximate, microbiological and sensory composition. All parameters evaluated in the proximate composition showed a significant difference (P